POLYVINYL ALCOHOL/POLYVINYL CHLORIDE (PVA/PVC) HOLLOW FIBER COMPOSITE NANOFILTRATION MEMBRANES FOR WATER TREATMENT - Alsalhy, Qusay; Figoli, A.; Algebory, Sufyan; M. Alwan, Ghanim; Simone, S.; Drioli, E. (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
Two different polyvinyl alcohol/polyvinyl chloride (PVA/PVC) hollow fiber composite nanofiltration membranes were prepared after PVC hollow fiber membranes were coated using dip-coating method with PVA aqueous solution, which was composed of PVA, fatty alcohol polyoxyethylene ether (AEO9), and water [PVA/AEO9/water (4:0.5:95.5) wt%]. Effect of two different PVC hollow fiber immersion times in coating solution were studied. Cross-section, internal and external surfaces of the PVC hollow fibers and PVA/PVC composite nanofiltration membranes structures were characterized by scanning electron microscopy (SEM), pure water permeation flux and solutes rejection. It was found that, the coating layer thickness on the outer surface of the 19 wt% PVC hollow fiber was thin and about (6μm), while the coating solution penetrates through the outer edge of the PVC hollow fiber and it looks like sponge-like structure with increase of the dip-coating time from 20 to 30 sec. Besides, the pure water permeation flux decreases and solutes rejection increases with an increase of the coating time from 20 to 30 sec for the two PVA/PVC composite nanofiltration membranes. Molecular weight cut-off (MWCO) of the PVA/PVC composite nanofiltration membranes were in the range of NF (i.e. 200-3000 Mw).